Comparative analysis of rural community pharmacy practice in Western Australia in 2002 and 2006 - Wibowo, Y.; Berbatis, Constantine; Joyce, A.; Sunderland, Bruce (Society of Pharmacy Practice and Research, 2012)
Background: Data are lacking on the characteristics of rural and remote community pharmacies in Western Australia (WA). Aim: To analyse characteristics of community pharmacies and pharmacists in rural WA in 2006 and to compare these with the results of a national survey conducted in 2002. Method: A survey was conducted in 2006 using a questionnaire similar to that used in a national survey conducted in 2002. The questionnaires were mailed to all 103 rural pharmacies in WA, of which 51 were returned (response rate 50%). Chi2 tests were used to compare the 2002 (rural WA) and 2006 data. Results: Pharmacist demographic characteristics were mostly unchanged. A trend towards increased employment of younger female pharmacists was found in 2006. 60% of respondents devoted less than 5 hours per month to continuing pharmacy education in both surveys. There were no significant differences in the characteristics of pharmacies in terms of PhARIA location, setting, banner group membership, inclusion of counselling areas, operations, trading hours and annual turnover. Pharmacies accredited by the Quality Care Pharmacy Program (QCCP) increased from 42% in 2002 to 86% in 2006. Conclusion: Many characteristics of rural WA pharmacies and pharmacists in 2006 were similar to 2002. Increased QCCP accreditations indicated higher quality assurance of rural pharmacy practice. The low uptake of ‘forward pharmacy’ in rural pharmacies warrants further evaluation.